The role of physical formidability in human social status allocation. [article]. - Lukaszewski, Aaron W.
Why are physically formidable men willingly allocated higher social status by others in cooperative groups? Ancestrally, physically formidable males would have been differentially equipped to generate benefits for groups by providing leadership services of within-group enforcement (e.g., implementing punishment of free riders) and between-group representation (e.g., negotiating with other coalitions). Therefore, we hypothesize that adaptations for social status allocation are designed to interpret men's physical formidability as a cue to these leadership abilities, and to allocate greater status to formidable men on this basis. These hypotheses were supported in 4 empirical studies wherein young adults rated standardized photos of subjects (targets) who were described as being part of a white-collar business consultancy. In Studies 1 and 2, male targets' physical strength positively predicted ratings of their projected status within the organization, and this effect was mediated by perceptions that stronger men possessed greater leadership abilities of within-group enforcement and between-group representation. Moreover, (a) these same patterns held whether status was conceptualized as overall ascendancy, prestige-based status, or dominance-based status, and (b) strong men who were perceived as aggressively self-interested were not allocated greater status. Finally, 2 experiments established the causality of physical formidability's effects on status-related perceptions by manipulating targets' relative strength (Study 3) and height (Study 4). In interpreting our findings, we argue that adaptations for formidability-based status allocation may have facilitated the evolution of group cooperation in humans and other primates.-- (from the authors)
Keywords: Simmons, Zachary L; Anderson, Cameron; Roney, James R; Cooperation; Dominance; Hierarchy; Prestige; Status